Stock assessment of the spiny lobster PanuUrus polyphagus (Herbst) off north-west coast of India - Kagwade, P V (Indian Journal of Fisheries, 2011)
The fishery of PanuUrus polyphagus has demonstraled successive periodic decline and revival.It has been able to survive for over 1 1/2 decades in spite of heavy exploitation. The present yields are503.5 tonnes for males and 825.4 tonnes for females, while the MSY are 520.365 tonnes for the formerand 837.8249 tonnes for the latter. The fishing effort would have to be reduced by 40% to reach theMSY level. Exploitation rate is 0.5096 for males and 0.4925 for females. Protecting the spawners eitherby banning their capture or by throwing them back into the sea during September, their peak spawningmonth, has been suggested as a small conservation measure.